Electrolyte additive, electrolyte, copper foil and preparation method and application of copper foil
By using specific additives in the electrolyte to regulate grain size and surface roughness, the problem of insufficient tensile strength and elongation of copper foil under thinness is solved, and the combination of high tensile strength and high elongation is achieved, improving the The performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411400027.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
AI Technical Summary
The existing copper foils are insufficient tensile strength and elongation under thin conditions, and cannot have both high performance, making it difficult to meet the needs of lithium-ion batteries.
Using an electrolyte additive, including sodium polydithiodipropane sulfonate, sodium alcohol thiopropane sulfonate, isothiourea propyl sulfate, polymer glue and thiourea compound, by regulating its ratio in the electrolyte The process of synergistic interaction between them can prevent the growth of grain nucleation, refine grain size, increase toughness, reduce surface roughness, and perform electrodeposition to prepare copper foil.
Significantly improve the tensile strength and elongation of copper foil, the tensile strength of the room temperature is ≥640MPa, the elongation is ≥5.0%, and the roughness of the breast surface is reduced, which solves the problem of mutual restraint between high tensile strength and high elongation, and improves lithium Performance of ion batteries.
Smart Images

Figure CN119307989A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrolyte additive, an electrolyte, a copper foil and a preparation method and application thereof. Background Art
[0002] Copper foil is a negative electrode current collector used in lithium-ion batteries. It has the characteristics of high conductivity, high tensile strength and good formability. It is widely used in new energy vehicles, 3C digital and energy storage. In recent years, the national and local governments have formulated a series of documents and measures to encourage and support the development of new energy vehicles and copper foil industries. For example, on the one hand, the government has increased subsidies for new energy vehicles and improved purchase tax exemption policies, which has provided favorable support for the development of the copper foil industry; on the other hand, the continuous expansion of the electric vehicle market and the energy storage market has also continued to grow the demand for copper foil. With the current development of electronic products towards miniaturization, lightweight design and enhanced functions, the trend of extremely thin copper foil is obvious, but the tensile strength and elongation of the thinner copper foil in the existing technology are not enough to meet the needs of lithium-ion batteries.
[0003] In the copper foil preparation process, the type and content of additives are important factors that determine the performance of the copper foil. In the prior art copper foil preparation process, there is a mutual restraint between the tensile strength and elongation of the copper foil, which affects the overall quality of the copper foil and makes it impossible to achieve high-quality copper foil with both high tensile strength and high elongation.
[0004] Therefore, how to make copper foil thinner while having good elongation and tensile strength is still an issue that needs to be studied urgently. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of low tensile strength and elongation of copper foil in the prior art, and to provide an electrolyte additive, electrolyte, copper foil and preparation method and application thereof. The present invention can significantly improve the tensile strength and elongation of copper foil, thereby greatly improving the performance of copper foil.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an electrolyte additive, which includes: sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds.
[0007] A second aspect of the present invention provides an electrolyte, wherein the electrolyte contains the additive of the present invention, and the content of the additive is 0.01-1 g / L based on the total mass of the electrolyte.
[0008] A third aspect of the present invention provides a method for preparing copper foil, the method comprising: subjecting the electrolyte of the present invention to electroplating to obtain copper foil.
[0009] The fourth aspect of the present invention provides a copper foil obtained by the preparation method of the present invention, wherein the room temperature tensile strength of the copper foil is ≥640MPa, and the elongation is ≥5.0%; the roughness of the matte surface of the copper foil has a Ra value ≤0.14μm, and a Rz value ≤1.4μm.
[0010] A fifth aspect of the present invention provides an application of the copper foil as an electrode current collector in a lithium battery.
[0011] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0012] (1) The present invention regulates the types of electrolyte additives and their appropriate ratios so that the additives act synergistically in the electrolyte, thereby hindering the nucleation and growth of grains, refining the grain size, increasing toughness, changing the microstructure and morphology of the coating, and reducing the surface roughness, so that the roughness Ra value of the rough surface of the copper foil is ≤0.14μm and the Rz value is ≤1.4μm, thereby further improving the tensile strength and elongation of the copper foil.
[0013] (2) The copper foil prepared by the electrolyte of the present invention has both high tensile strength and high elongation, with a room temperature tensile strength of ≥640 MPa and an elongation of ≥5.0%, thus overcoming the disadvantage that high tensile strength and high elongation restrain each other. The copper foil can be applied to the production of lithium-ion batteries to greatly improve their performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a distribution diagram of large and small grain boundaries of the copper foil prepared in Example 1 of the present invention;
[0015] Figure 2 The electron backscatter diffraction (EBSD) image of the cross section of the copper foil prepared in Example 1 of the present invention;
[0016] Figure 3 This is a grain size diagram of the copper foil prepared in Example 1 of the present invention;
[0017] Figure 4 The IPF diagram (inverse pole figure) of the copper foil prepared in Example 1 of the present invention;
[0018] Figure 5 This is a SEM image of the surface morphology of the copper foil prepared in Example 1 of the present invention;
[0019] Figure 6 This is a SEM image of the surface morphology of the copper foil prepared in Comparative Example 1 of the present invention;
[0020] Figure 7 This is a SEM image of the surface morphology of the copper foil prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.
[0023] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0024] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those conventionally used in the art when the present invention was proposed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0025] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.
[0026] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0027] The present invention provides an electrolyte additive, which includes sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds. The copper foil prepared by using the electrolyte additive has both high tensile strength and high elongation, and has good industrial prospects.
[0028] In the present invention, the sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds are all commercially available products and can be purchased through commercial channels.
[0029] In the present invention, the types of the thiourea compounds can be selected from a wide range, which are exemplified below, but are not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the thiourea compound is selected from one or more of formula (I), formula (II) and formula (III):
[0030]
[0031] In the present invention, the substituent groups of R1, R2, R3, and R4 can be selected from a wide range, for example, R1, R2, R3, and R4 can be independently selected from hydrogen, C1-C8 alkyl, C1-C8 acyl, amino, and aniline. The C1-C8 alkyl refers to an alkyl containing 1-8 carbons, which can be a straight-chain alkyl or a branched alkyl; the C1-C8 acyl refers to an acyl containing 1-8 carbons, which can be a straight-chain acyl or a branched acyl. The above is an exemplary description, but it does not limit the scope of the present invention. The copper foil prepared by the thiourea compound electrolyte additive using the above-mentioned substituent groups has high tensile strength and high elongation.
[0032] According to a preferred embodiment of the present invention, R1, R2, R3, and R4 are independently selected from hydrogen, C1-C5 straight-chain alkyl, C1-C5 straight-chain acyl, amino, and aniline. The above is exemplary, but does not limit the scope of the present invention.
[0033] According to a preferred embodiment of the present invention, at least two of R1, R2, R3 and R4 are hydrogen. The above description is exemplary, but does not limit the scope of the present invention.
[0034] In the present invention, the substituent groups of R5 and R6 can be selected from a wide range, for example, R5 and R6 can be independently selected from hydrogen, C1-C8 alkyl, C1-C8 acyl, amino, and aniline. The C1-C8 alkyl refers to an alkyl containing 1-8 carbons, which can be a straight-chain alkyl or a branched alkyl; the C1-C8 acyl refers to an acyl containing 1-8 carbons, which can be a straight-chain acyl or a branched acyl. The above is an exemplary description, but it does not limit the scope of the present invention. The copper foil prepared by the thiourea compound electrolyte additive using the above-mentioned substituent groups has high tensile strength and high elongation.
[0035] According to a preferred embodiment of the present invention, R5 and R6 are independently selected from hydrogen, C1-C5 straight-chain alkyl, C1-C5 straight-chain acyl, amino, and aniline. The above is exemplary, but does not limit the scope of the present invention.
[0036] According to a preferred embodiment of the present invention, at least one of R5 and R6 is hydrogen. The above description is exemplary, but does not limit the scope of the present invention.
[0037] In the present invention, the substituent group of R7 can be selected from a wide range, for example, R7 is selected from one of hydrogen, amino, acyl and phenyl. In the embodiment of the present invention, R7 is phenyl as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereby.
[0038] In the present invention, the substituent groups of R8 and R9 can be selected from a wide range, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, R8 and R9 are independently selected from hydrogen and / or C1-C8 alkyl. In the embodiments of the present invention, hydrogen is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto. The copper foil prepared by the thiourea compound electrolyte additive using the above-mentioned substituent groups has high tensile strength and high elongation.
[0039] According to a preferred embodiment of the present invention, R8 and R9 are independently selected from hydrogen and / or a C1-C5 straight chain alkyl group. The above is exemplary but does not limit the scope of the present invention.
[0040] According to a preferred embodiment of the present invention, at least one of R8 and R9 is hydrogen. The above description is exemplary, but does not limit the scope of the present invention.
[0041] In the present invention, any thiourea compound that meets the above requirements can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the thiourea compound is selected from:
[0042]
[0043] or more.
[0044] In the present invention, any thiourea compound that meets the above requirements can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the thiourea compound is selected from one or more of methylthiourea, ethylthiourea, n-hexylthiourea, N,N-dimethylthiourea, N-acetylthiourea, thiosemicarbazide, dithizone and 3-mercapto-1,2,4-triazole. The above is exemplary, but does not limit the scope of the present invention.
[0045] According to a preferred embodiment of the present invention, the thiourea compound is selected from methylthiourea and 3-mercapto-1,2,4-triazole, and the content of methylthiourea and 3-mercapto-1,2,4-triazole is 40-60% by weight respectively. The aforementioned thiourea compound additives are used to synergistically act in the electrolyte to hinder the nucleation and growth of grains, refine the grain size, increase toughness, change the microstructure and morphology of the coating, and reduce the surface roughness, so that the roughness Ra value of the prepared copper foil is ≤0.14μm, the Rz value is ≤1.4μm, the tensile strength at room temperature is ≥640MPa, and the elongation is ≥5.0%. When applied to the production of lithium-ion batteries, its performance can be greatly improved.
[0046] In the present invention, the polymer glue is collagen, and there is no special limitation on the collagen. The collagen commonly used in the art can be used in the present invention. The following exemplary description does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the weight average molecular weight of the collagen is 5000-15000 g / mol.
[0047] In the present invention, the mass ratio of the sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds can be selected in a wide range. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the mass ratio of the sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds is 1-50: 1-50: 1-50: 1-60: 1-60; preferably 5-40: 1-30: 1-30: 5-40: 1-30. The content of electrolyte additives is an important factor in determining the performance of copper foil prepared therefrom. The copper foil prepared by using the aforementioned preferred sodium polydisulfide propane sulfonate, sodium thiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compound as electrolyte additives has both high tensile strength and high elongation, with a room temperature tensile strength of ≥640MPa and an elongation of ≥5.0%, overcoming the disadvantage of the mutual restraint between high tensile strength and high elongation. The copper foil can be greatly improved by being applied to the production of lithium-ion batteries.
[0048] The present invention provides an electrolyte, wherein the electrolyte contains the additive of the present invention, and the content of the additive is 0.01-1 g / L, preferably 0.03-0.2 g / L, based on the total mass of the electrolyte. The copper foil prepared by using the electrolyte has high tensile strength and high elongation.
[0049] In the present invention, the composition of the electrolyte can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the electrolyte further contains a copper-containing inorganic salt, an oxygen-containing acid source of sulfur, a chlorine-containing compound source and a solvent.
[0050] In the present invention, there is no special requirement for the copper-containing inorganic salt. The following exemplary description is given, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, the copper-containing inorganic salt is selected from one or more of copper sulfate, copper nitrate and copper chloride, preferably copper sulfate, and more preferably copper sulfate pentahydrate. For example, in the embodiments of the present invention, copper sulfate pentahydrate is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereby.
[0051] In the present invention, the oxygen-containing acid source of sulfur is added in order to better dissolve the copper-containing inorganic salt. There is no special requirement for the oxygen-containing acid source of sulfur. For example, it is generally selected from one or more of sulfuric acid, sulfurous acid, hyposulfurous acid, persulfuric acid, and pyrosulfuric acid, preferably sulfuric acid, and more preferably concentrated sulfuric acid. In the embodiment of the present invention, the oxygen-containing acid source of sulfur is sulfuric acid with a mass concentration of 98wt% as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereby.
[0052] In the present invention, there is no special requirement for the chlorine-containing compound source. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the chlorine-containing compound source is selected from one or more of hydrochloric acid, sodium chloride, potassium chloride, and copper chloride, preferably hydrochloric acid, and more preferably dilute hydrochloric acid with a mass fraction of 36-38wt%. In the embodiment of the present invention, the chlorine-containing compound source uses hydrochloric acid with a mass concentration of 37wt% as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.
[0053] In the present invention, there is no special requirement for the solvent of the electrolyte, and commonly used electrolyte solvents can be used in the present invention. The following exemplary description does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the solvent is selected from one or more of water, methanol, and glycerol, preferably water. The solvent of the electrolyte in the embodiment of the present invention is water.
[0054] In the present invention, the specific composition and dosage of the electrolyte can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the mass ratio of the copper-containing inorganic salt to the sulfur-containing oxygen-containing acid source is 0.1-10, preferably 0.5-5.
[0055] In the present invention, the mass ratio of the copper-containing inorganic salt to the chlorine-containing compound source can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the mass ratio of the copper-containing inorganic salt to the chlorine-containing compound source is 1000-150000, preferably 3000-40000.
[0056] In the present invention, the mass ratio of the copper-containing inorganic salt to the additive can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of the copper-containing inorganic salt to the additive is 100-100000, for example, 100, 200, 500, 1000, 2000, 5000, 10000, 20000, 50000, 100000, etc., preferably 500-10000.
[0057] In the present invention, there is no special requirement for the amount of the solvent, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the amount of the added solvent is such that the concentration of the copper-containing inorganic salt is 80 g / L-400 g / L. The solvent includes solvents introduced from other raw materials.
[0058] The electrolyte having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention. There is no special requirement for its preparation method. The following exemplary description is not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the preparation method of the electrolyte of the present invention is, for example:
[0059] 1) Mixing a copper-containing inorganic salt, a sulfur-containing oxygen acid source, and a chlorine-containing compound source in the presence of a solvent;
[0060] 2) Add the additives sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds to step 1), mix, and then adjust the volume in a 1 L volumetric flask.
[0061] In the present invention, there is no special requirement for the mixing method, and commonly used mixing methods can be used in the present invention. For example, in the embodiments of the present invention, stirring and mixing with a magnetic stirrer is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereby.
[0062] In the present invention, in step 1), there is no special requirement for the mixing temperature, as long as the mixture is fully dissolved and mixed. The general mixing temperature is 25-60° C. The above is an exemplary description, but does not limit the scope of the present invention.
[0063] In the present invention, there is no special requirement for the mixing time, which is adjusted according to the mixing temperature. For example, the general mixing time is 5-40 minutes. In the present invention, stirring for 15 minutes is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.
[0064] The invention provides a method for preparing copper foil, which comprises: subjecting the electrolyte of the invention to electroplating to obtain the copper foil.
[0065] In the present invention, the conditions for the electroplating can be selected in a wide range, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the electroplating uses a titanium plate as a cathode and an iridium-coated titanium plate as an anode, and direct current is used for electroplating.
[0066] In the present invention, there is no special requirement for the iridium-coated titanium plate. For example, the iridium-coated titanium plate of the present invention is a commercially available product, but the scope of the present invention is not limited thereby.
[0067] According to a preferred embodiment of the present invention, the electrodeposition current density is 5-40A / dm 2 , preferably 10-30A / dm 2 The above description is for exemplary purposes only, but does not limit the scope of the present invention.
[0068] According to a preferred embodiment of the present invention, the electrodeposition temperature is 25-80°C, preferably 40-60°C. For example, in the embodiments of the present invention, the electrodeposition temperatures of 25°C, 35°C, 45°C, 50°C and 57°C are used as examples to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.
[0069] In the present invention, the electrodeposition time can be selected in a wide range, and is specifically adjusted according to the electrodeposition current density and the electrodeposition temperature. For example, the general time is 50-400s, preferably 60-200s. The above is exemplary, but does not limit the scope of the present invention.
[0070] In the present invention, in order to improve the antioxidant ability of copper foil, anti-oxidation treatment is generally performed. This is well known to those skilled in the art. There is no special requirement for the anti-oxidation treatment. The following is an exemplary description, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the anti-oxidation treatment is fully immersed in a phytic acid solution. In the embodiment of the present invention, the anti-oxidation treatment is immersed in a phytic acid solution with a mass fraction of 3%-5% as an exemplary embodiment to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.
[0071] In the present invention, there is no special requirement for the time of the anti-oxidation treatment, for example, the general time is 1-10 seconds. In the embodiment of the present invention, the time of the anti-oxidation treatment is 5 seconds as an example to illustrate the advantages of the present invention, but it does not limit the scope of the present invention.
[0072] In the present invention, there is no special requirement for the post-treatment method of the copper foil after soaking in the phytic acid solution, for example, the copper foil obtained after soaking is blown dry for standby use.
[0073] The present invention provides a copper foil obtained by the preparation method of the present invention, wherein the room temperature tensile strength of the copper foil is ≥640MPa, and the elongation is ≥5.0%; the roughness of the rough surface of the copper foil Ra is ≤0.14μm, and the Rz value is ≤1.4μm. The copper foil prepared by the present invention has both high tensile strength and high elongation, and can be applied to the production of lithium ion batteries to greatly improve their performance.
[0074] The present invention provides an application of the copper foil as an electrode current collector in a lithium battery.
[0075] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0076] (1) The present invention adjusts the appropriate ratio between the additives so that the additives act synergistically in the electrolyte, thereby hindering the nucleation and growth of grains, refining the grain size, increasing the toughness, changing the microstructure and morphology of the coating, and reducing the surface roughness, so that the roughness Ra value of the rough surface of the copper foil is ≤0.14μm, and the Rz value is ≤1.4μm, thereby further improving the tensile strength and elongation of the copper foil.
[0077] (2) The copper foil prepared by the present invention has both high tensile strength and high elongation, with a room temperature tensile strength of ≥640 MPa and an elongation of ≥5.0%, thus overcoming the disadvantage that high tensile strength and high elongation restrain each other. The copper foil can be applied to the production of lithium-ion batteries to greatly improve their performance.
[0078] The present invention is described in detail below through examples. The sulfur-containing oxygen acid source used in the examples and comparative examples has a mass concentration of 98 wt% sulfuric acid, and the chlorine-containing compound source used has a mass concentration of 37 wt% hydrochloric acid; the copper foils prepared in the examples and comparative examples are subjected to the same anti-oxidation treatment, which is soaked in a phytic acid solution with a mass fraction of 5% for 5 seconds and then taken out and blown dry.
[0079] In the embodiments and comparative examples of the present invention, the raw material copper sulfate pentahydrate is a commercially available product of Xilong Scientific Chemical Industry, Sinopharm Group.
[0080] In the copper foil performance test, the copper foil to be tested is required to have no wrinkles (no wavy edges, burrs or notches should appear when cutting samples with a cutter); the surface roughness Ra and Rz are measured using a roughness meter, and the tensile strength and elongation are measured using a universal testing machine; the large and small grain boundary distribution of the copper foil, the electron backscatter diffraction (EBSD) diagram of the copper foil cross section, the grain size of the copper foil, and the IPF diagram (inverse pole figure) of the copper foil are all measured using an electron backscatter diffractometer.
[0081] Example 1
[0082] (1) When the temperature of the magnetic stirrer is 45°C, copper sulfate pentahydrate is added to 500g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 312g, the mass of sulfuric acid (including solvent) is 105g, and the mass of hydrochloric acid (including solvent) is 67mg.
[0083] (2) Weigh 10 mg of sodium polydisulfide propane sulfonate, 2 mg of sodium alcoholthiopropane sulfonate, 5 mg of isothiourea propyl sulfate, 20 mg of collagen (molecular weight: 10000 g / mol), and 2 mg of ethylthiourea. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.039 g / L based on the total mass of the electrolyte.
[0084] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 45°C and a current density of 10 A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 79s.
[0085] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0086] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0087] The prepared copper foil was subjected to electron backscatter diffraction test, and the test results are as follows: Figure 1-4 As shown, Figure 1 It can be seen that there are a large number of twin boundaries inside the copper foil (the red line part in the figure), and the red accounts for 77.3%. The high-density twins are conducive to the bidirectional improvement of the tensile strength and elongation of the copper foil; Figure 2 It can be seen that the high-angle grain boundaries account for 98.8%, which can effectively prevent the movement of dislocations, increase the crystal energy, improve the recrystallization fraction, refine the grains, and significantly increase the tensile strength of the copper foil; Figure 3 It can be seen that the average grain size of the copper foil is only 0.4μm. Under the effect of fine grain strengthening, the tensile strength of the copper foil can be greatly improved. Figure 4 It can be seen that the (101) crystal plane appears red, indicating that there is obvious preferential orientation of the copper foil crystal plane (220). The enhancement of the preferential orientation of the copper foil crystal plane (220) is beneficial to the improvement of the tensile strength of the copper foil.
[0088] The prepared copper foil was subjected to SEM test, and the test results are as follows Figure 5 As shown, Figure 5The surface of the copper foil is flat without peaks and valleys, the grains are fine, and there are no sharp peaks. This indicates that during the electrodeposition process, the electrolyte additives of the present invention inhibit or promote each other and jointly play a "fine grain strengthening" role, which is beneficial to improving the tensile strength and elongation of the lithium battery copper foil.
[0089] Example 2
[0090] (1) When the temperature of the magnetic stirrer is 35°C, copper sulfate pentahydrate is added to 600g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 339g, the mass of sulfuric acid (including solvent) is 132g, and the mass of hydrochloric acid (including solvent) is 49mg.
[0091] (2) Weigh 20 mg of sodium polydisulfide propane sulfonate, 5 mg of sodium alcoholthiopropane sulfonate, 3 mg of isothiourea propyl sulfate, 20 mg of collagen (molecular weight: 10000 g / mol), and 6 mg of N,N-dimethylthiourea. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.054 g / L based on the total mass of the electrolyte.
[0092] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 35°C and a current density of 15 A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 73s.
[0093] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0094] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0095] Example 3
[0096] (1) When the temperature of the magnetic stirrer is 50°C, copper sulfate pentahydrate is added to 450g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 273g, the mass of sulfuric acid (including solvent) is 120g, and the mass of hydrochloric acid (including solvent) is 56mg.
[0097] (2) Weigh 5 mg of sodium polydisulfide propane sulfonate, 8 mg of sodium alcoholthiopropane sulfonate, 10 mg of isothiourea propyl sulfate, 30 mg of collagen (molecular weight: 10000 g / mol), and 10 mg of N-acetylthiourea. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.063 g / L based on the total mass of the electrolyte.
[0098] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 50°C and a current density of 25A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 89s.
[0099] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0100] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0101] Example 4
[0102] (1) When the temperature of the magnetic stirrer is 25°C, copper sulfate pentahydrate is added to 470g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 292g, the mass of sulfuric acid (including solvent) is 144g, and the mass of hydrochloric acid (including solvent) is 63mg.
[0103] (2) Weigh 6 mg of sodium polydisulfide propane sulfonate, 10 mg of sodium alcoholthiopropane sulfonate, 15 mg of isothiourea propyl sulfate, 35 mg of collagen (molecular weight: 10000 g / mol), and 8 mg of N,N-dimethylthiourea. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.074 g / L based on the total mass of the electrolyte.
[0104] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 25°C and a current density of 30 A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 95s.
[0105] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0106] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0107] Example 5
[0108] (1) When the temperature of the magnetic stirrer is 50°C, copper sulfate pentahydrate is added to 800g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 234g, the mass of sulfuric acid (including solvent) is 120g, and the mass of hydrochloric acid (including solvent) is 38mg.
[0109] (2) Weigh 20 mg of sodium polydisulfide propane sulfonate, 10 mg of sodium alcoholthiopropane sulfonate, 10 mg of isothiourea propyl sulfate, 40 mg of collagen (molecular weight: 10000 g / mol), and 12 mg of n-hexylthiourea. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.092 g / L based on the total mass of the electrolyte.
[0110] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 50°C and a current density of 25A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 93s.
[0111] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0112] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0113] Example 6
[0114] (1) When the temperature of the magnetic stirrer is 35°C, copper sulfate pentahydrate is added to 700g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 269g, the mass of sulfuric acid (including solvent) is 90g, and the mass of hydrochloric acid (including solvent) is 54mg.
[0115] (2) Weigh 12 mg of sodium polydisulfide propane sulfonate, 2 mg of sodium alcoholthiopropane sulfonate, 6 mg of isothiourea propyl sulfate, 25 mg of collagen (molecular weight: 10000 g / mol), and 2 mg of 3-mercapto-1,2,4-triazole. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additive is 0.047 g / L based on the total mass of the electrolyte.
[0116] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 35°C and a current density of 15 A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 77s.
[0117] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0118] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0119] Example 7
[0120] (1) When the temperature of the magnetic stirrer is 45°C, copper sulfate pentahydrate is added to 650g of deionized water, and sulfuric acid and hydrochloric acid are added during stirring until they are completely mixed. The mass of copper sulfate pentahydrate is 369g, the mass of sulfuric acid (including solvent) is 80g, and the mass of hydrochloric acid (including solvent) is 50mg.
[0121] (2) Weigh 8 mg of sodium polydisulfide propane sulfonate, 4 mg of sodium alcoholthiopropane sulfonate, 6 mg of isothiourea propyl sulfate, 20 mg of collagen (molecular weight: 10000 g / mol), and 5 mg of thiosemicarbazide. Add the additives to the solution of step (1) in sequence, continue stirring for 15 min, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.043 g / L based on the total mass of the electrolyte.
[0122] (3) The electrolyte was placed in an electrolytic cell, with the titanium plate as the cathode and the iridium-coated titanium plate as the anode. Direct current deposition was used at a temperature of 45°C and a current density of 10 A / dm 2 , copper foil was obtained under the conditions of electrodeposition time of 75s.
[0123] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0124] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0125] Example 8
[0126] (1) When the temperature of the magnetic stirrer is 57°C, add copper sulfate pentahydrate to 550g of deionized water, add sulfuric acid and hydrochloric acid during stirring, and wait for them to be completely mixed. The mass of copper sulfate pentahydrate is 232g, the mass of sulfuric acid (including solvent) is 70g, and the mass of hydrochloric acid (including solvent) is 50mg.
[0127] (2) Weigh 12 mg of sodium polydisulfide propane sulfonate, 3 mg of sodium alcoholthiopropane sulfonate, 3 mg of isothiourea propyl sulfate, 30 mg of collagen (molecular weight: 10000 g / mol), and 6 mg of dithizone. Add the additives to the solution of step (1) in sequence, continue stirring for 15 minutes, and then adjust the volume in a 1 L volumetric flask to obtain an electrolyte, wherein the content of the additives is 0.054 g / L based on the total mass of the electrolyte.
[0128] (3) The electrolyte is placed in an electrolytic cell, a titanium plate is used as a cathode, an iridium-coated titanium plate is used as an anode, and direct current deposition is adopted to obtain a copper foil at a temperature of 57° C., a current density of 10 A / dm2, and an electrodeposition time of 69 s.
[0129] (4) The obtained copper foil is subjected to an anti-oxidation treatment and then set aside.
[0130] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0131] Example 9
[0132] The method and steps of Example 1 are followed, except that the thiourea compound in the additive is a mixture of methylthiourea and 3-mercapto-1,2,4-triazole, wherein methylthiourea is 1 mg and 3-mercapto-1,2,4-triazole is 1 mg. The prepared copper foil is subjected to performance tests, and the test results are shown in Table 1.
[0133] Example 10
[0134] The method and steps of Example 1 were followed, except that 50 mg of sodium polydisulfide propane sulfonate, 50 mg of sodium thiopropane sulfonate, 40 mg of isothiourea propyl sulfate, 50 mg of collagen (molecular weight: 10000 g / mol), and 40 mg of ethylthiourea were weighed. The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0135] Comparative Example 1
[0136] The method and steps of Example 1 are followed, except that ethylthiourea is not added to the additives, wherein 10 mg of sodium polydisulfide propane sulfonate, 2 mg of sodium thiopropane sulfonate, 7 mg of isothiourea propyl sulfate, and 20 mg of collagen (molecular weight: 10000 g / mol) are added.
[0137] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0138] The prepared copper foil was subjected to SEM test, and the test results are as follows Figure 6 As shown, Figure 6 There are obvious cracks on the surface of the copper foil. The reason may be that the additive formula fails to inhibit the deposition rate of copper ions, resulting in some grains not being fully nucleated and new grains starting to grow.
[0139] Comparative Example 2
[0140] The method and steps of Example 1 are followed, except that sodium thiopropane sulfonate is not added to the additives, wherein 10 mg of sodium polydisulfide propane sulfonate, 7 mg of isothiourea propyl sulfate, 20 mg of collagen (molecular weight: 10000 g / mol), and 2 mg of ethylthiourea are included.
[0141] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0142] The prepared copper foil was subjected to SEM test, and the test results are as follows Figure 7 As shown, Figure 7The surface of the copper foil is obviously uneven, similar to a horseshoe print, which increases the roughness, reduces the tensile strength and elongation, and is prone to breakage during application, affecting product performance.
[0143] Comparative Example 3
[0144] The method and steps of Example 1 are followed, except that isothiourea propyl sulfate is not added to the additives, wherein 10 mg of sodium polydisulfide propane sulfonate, 2 mg of sodium alcoholthiopropane sulfonate, 20 mg of collagen (molecular weight: 10000 g / mol), and 7 mg of ethylthiourea are added.
[0145] The prepared copper foil was subjected to performance tests, and the test results are shown in Table 1.
[0146] Table 1
[0147]
[0148] It can be seen from the results in Table 1 that the copper foil prepared by the present invention has a tensile strength of ≥640MPa and an elongation of ≥5.0%; the roughness of the rough surface of the copper foil Ra value is ≤0.14μm, and the Rz value is ≤1.40μm. It has excellent mechanical properties, solves the technical problem that the two properties of high tensile strength and high elongation of the lithium battery copper foil in the prior art cannot be achieved at the same time, and is conducive to the development of lithium battery copper foil.
[0149] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrolyte additive, characterized in that: The additives include: sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue, and thiourea compounds.
2. The additive according to claim 1, wherein The thiourea compound is selected from one or more of formula (I), formula (II) and formula (III): Wherein, R1, R2, R3, and R4 are independently selected from hydrogen, C1-C8 alkyl, C1-C8 acyl, amino, and anilino; Preferably, R1, R2, R3, and R4 are independently selected from hydrogen, C1-C5 straight-chain alkyl, C1-C5 straight-chain acyl, amino, and anilino; Preferably, at least two of R1, R2, R3, and R4 are hydrogen; and / or R5 and R6 are independently selected from hydrogen, C1-C8 alkyl, C1-C8 acyl, amino, and anilino; Preferably, R5 and R6 are independently selected from hydrogen, C1-C5 straight-chain alkyl, C1-C5 straight-chain acyl, amino, and anilino; Preferably, at least one of R5 and R6 is hydrogen; and / or R7 is selected from one of hydrogen, amino, acyl and phenyl; and / or R8, R9 are independently selected from hydrogen and / or C1-C8 alkyl; Preferably, R8 and R9 are independently selected from hydrogen and / or C1-C5 straight chain alkyl; Preferably, at least one of R8 and R9 is hydrogen.
3. The additive according to claim 1 or 2, wherein The thiourea compound is selected from one or more of methylthiourea, ethylthiourea, n-propylthiourea, n-butylthiourea, n-hexylthiourea, N,N-dimethylthiourea, N-acetylthiourea, N-benzoylthiourea, thiosemicarbazide, dithizone, and 3-mercapto-1,2,4-triazole; Preferably, The thiourea compound is selected from one or more of methylthiourea, ethylthiourea, n-hexylthiourea, N,N-dimethylthiourea, N-acetylthiourea, thiosemicarbazide, dithizone and 3-mercapto-1,2,4-triazole; More preferably, The thiourea compounds are methylthiourea and 3-mercapto-1,2,4-triazole, and the content of methylthiourea and 3-mercapto-1,2,4-triazole is 40-60% by weight respectively.
4. The additive according to any one of claims 1 to 3, wherein The polymer glue is collagen, and the weight average molecular weight of the collagen is 5000-15000 g / mol; and / or The mass ratio of the sodium polydisulfide propane sulfonate, sodium alcoholthiopropane sulfonate, isothiourea propyl sulfate, polymer glue and thiourea compound is 1-50:1-50:1-50:1-60:1-60; preferably 5-40:1-30:1-30:5-40:1-30.
5. An electrolyte, characterized in that: The electrolyte contains the additive according to any one of claims 1 to 4, and the content of the additive is 0.01 to 1 g / L based on the total mass of the electrolyte.
6. The electrolyte according to claim 5, wherein The content of the additive is 0.03-0.2 g / L based on the total mass of the electrolyte; and / or The electrolyte also contains a copper-containing inorganic salt, an oxygen-containing acid source of sulfur, a chlorine-containing compound source, and a solvent; Preferably, The copper-containing inorganic salt is selected from one or more of copper sulfate, copper nitrate and copper chloride, preferably copper sulfate, more preferably copper sulfate pentahydrate; and / or The sulfur-containing oxygen acid source is selected from one or more of sulfuric acid, sulfurous acid, hyposulfurous acid, persulfuric acid, and pyrosulfuric acid, preferably sulfuric acid, more preferably concentrated sulfuric acid; and / or The chlorine-containing compound source is selected from one or more of hydrochloric acid, sodium chloride, potassium chloride, and copper chloride, preferably hydrochloric acid, more preferably dilute hydrochloric acid with a mass fraction of 36-38wt%; and / or The solvent is selected from one or more of water, methanol and glycerol, preferably water.
7. The electrolyte according to claim 6, wherein The mass ratio of the copper-containing inorganic salt to the sulfur-containing oxygen acid source is 0.1-10; preferably 0.5-5; and / or The mass ratio of the copper-containing inorganic salt to the chlorine-containing compound source is 1000-150000; preferably 3000-40000; and / or The mass ratio of the copper-containing inorganic salt to the additive is 100-100000; preferably 500-10000; and / or The concentration of the copper-containing inorganic salt is 80 g / L-400 g / L.
8. A method for preparing copper foil, characterized in that: The method includes: Electrodepositing the electrolyte according to any one of claims 5 to 7 to obtain a copper foil; Preferably, the electrodeposition conditions include: Electrodeposition using a titanium plate as cathode and an iridium-coated titanium plate as anode; and / or Electrodeposition current density is 5-40A / dm 2 , preferably 10-30A / dm 2 ; and / or The electrodeposition temperature is 25-80°C, preferably 40-60°C; and / or The electrodeposition time is 50-400 s, preferably 60-200 s.
9. A copper foil obtained by the preparation method according to claim 8, characterized in that: The copper foil has a room temperature tensile strength of ≥640MPa and an elongation of ≥5.0%; The roughness Ra value of the matte surface of the copper foil is ≤0.14 μm, and the Rz value is ≤1.4 μm.
10. Use of the copper foil according to claim 9 as an electrode current collector in a lithium battery.